2004
DOI: 10.1016/j.breast.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Secretory breast carcinoma—case report and review of the medical literature

Abstract: Summary Secretory breast carcinoma (SBC) is a rare type of invasive breast cancer. Since little is known about the biology of this rare tumour, it is useful to report every such case, in order to make as much information as possible available in the medical literature. We present the case of an 18-year-old woman with a SBC treated by mastectomy (Madden) and axillary node dissection (stage pT3N1M0) 1 followed by chemotherapy (FEC 2 regimen) and radiotherapy. The patient has meanwhile completed 4 years of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 4 publications
1
45
0
7
Order By: Relevance
“…These neoplasms have indolent clinical behavior, late local recurrences and prolonged survival, even with lymph node involvement. 3,4 Immunochemically, the tumor usually has shown strong reactivity for S-100 and is negative for estrogen receptor (ER), progesterone receptor (PR) and HER2. [4][5][6][7] In 2002, Tognon et al 8 were the first to report that secretory breast carcinoma expresses the ETV6-NTRK3 gene fusion in 12 out of 13 of their cases.…”
Section: Secretory Breast Carcinoma Was Originally Recognized In 1966mentioning
confidence: 99%
See 1 more Smart Citation
“…These neoplasms have indolent clinical behavior, late local recurrences and prolonged survival, even with lymph node involvement. 3,4 Immunochemically, the tumor usually has shown strong reactivity for S-100 and is negative for estrogen receptor (ER), progesterone receptor (PR) and HER2. [4][5][6][7] In 2002, Tognon et al 8 were the first to report that secretory breast carcinoma expresses the ETV6-NTRK3 gene fusion in 12 out of 13 of their cases.…”
Section: Secretory Breast Carcinoma Was Originally Recognized In 1966mentioning
confidence: 99%
“…3,4 Immunochemically, the tumor usually has shown strong reactivity for S-100 and is negative for estrogen receptor (ER), progesterone receptor (PR) and HER2. [4][5][6][7] In 2002, Tognon et al 8 were the first to report that secretory breast carcinoma expresses the ETV6-NTRK3 gene fusion in 12 out of 13 of their cases. Recently, Laé et al 7 demonstrated that secretory breast carcinoma with the ETV6-NTRK3 fusion gene belongs to the phenotypic spectrum of basal-like breast carcinomas, and immunohistochemical, as well as genetic features of secretory breast carcinomas, distinguished them from other basal-like breast cancers.…”
Section: Secretory Breast Carcinoma Was Originally Recognized In 1966mentioning
confidence: 99%
“…Distant metastases develop in ϳ10% of cases [2,3,18,40,55], and the survival rate is in the range of 85% to Ͼ90% (with a minimum of 5 years of follow-up) [3,17,18,40,55]. Extrapolating from ACC of the salivary glands, Ro et al [47] (n ϭ 12) stratified tumors into three grades based on the proportion of solid growth (grade I, no solid component; grade II, Ͻ30% solid; grade III, Ͼ30% solid) and suggested 21%-26% involved [4,29], although 51% in one series [28] 10% involved [7], usually Ͻ3 nodes involved [51] Up to 78% node negative at presentation [8, 9, 30- Better than IDC, NST [28] in some series 5-yr relative survival risk of 104% [1] Lower disease-free survival rate (41% versus 87%) and 5-yr survival rate (63% versus 92%) than with IDC of all subtypes [9] Poorer than other breast cancer histologies [11,33,34]; 5-yr survival rate, 50%-67% [11,21,33] Good [1,22,35]; Ͼ80% 5-yr survival rate [15,22,77] Good [23,37,78] Abbreviations: DCIS, ductal carcinoma in situ; ER, estrogen receptor; HER-2, human epidermal growth factor receptor 2; IDC, invasive ductal carcinoma; IHC, immunohistochemical; MeBC, metaplastic breast cancer; MRI, magnetic resonance imaging; NST, no special type; PR, progesterone receptor.…”
Section: Secretory Breast Cancermentioning
confidence: 99%
“…There is some controversy about the optimal surgical approach [38]. Local recurrences occurred in 33% of cases treated with breast-conserving surgery in one series (n ϭ 12) [75], and some authors advocate mastectomy [38,39,45,78,106] with lymph node sampling [16,38,45,107] as the primary surgical approach. Alternatively, it may be possible to consider breast-conserving surgery [23,37,45,107,108] provided that there are generous margins [23,45].…”
Section: Secretory Breast Cancermentioning
confidence: 99%
“…Secretory breast carcinoma has distinctive features that differ from other ductal carcinomas of breast, such as the presence of large amounts of intracellular and extracellular secretory material. These neoplasms can have late local recurrences but is generally associated with prolonged survival, even with axillary lymphnode involvement [3,4]. Immunochemically, the tumor usually shows strong reactivity for S-100 but is negative for estrogen receptor (ER), progesterone receptor (PR) and HER2 neu protein [5][6][7].…”
Section: Discussionmentioning
confidence: 99%